Kepemimpinan Klinik - Peran Dan Tantangan Manajer Rumah Sakit Dalam Peningkatan Mutu Pelayanan Kesehatan = Clinical Leadership-The Role And Challenge Of Hospital Manager In Improving The Quality Of Health Services - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Health systems worldwide recognize the need for clinicians to be closely involved in leadership and management decisions. The reasons have been well documented. The quality of healthcare is determined largely by the expert skills and knowledge of clinicians. Clinicians have a high level of professional freedom and discretion in their actions. Their clinical judgments largely determine current and future resource allocation decisions. As a result, health systems recognize the importance of involving clinicians in the management and leadership of health care organizations. This article contents that clinical leadership is a fundamental organizational competence in healthcare. It defines clinical leadership. It identifies and describes features of the context and process of clinical leadership. It analysis key aspects of leadership competence and reviews the constituents of this competence from a number of differing viewpoints.